Images of crime: empathetic newsworthiness and digital technologies in the production of police news on television in Argentina - Calzado, Mercedes (Theorizing criminality and policing in the digital media age, 2021)
Purpose: This chapter presents some results of a research project on the new modes of production of television crime news in Argentina. The authors explore the creation of content regarding crime in television newscasts, focusing on the ways of accessing the sources, circulation of information, and exhibition strategies. Methodology/approach: The enquiry involved interviews with news workers and observations in nine stations in Buenos Aires City. The authors describe the routines in the production of television crime news in Argentina, the ways of narrating and enunciating crime news on television, the role played by the police in the structure of the news, and the emergence of new sources of information. Findings: The authors outline three main findings: Most of the newscasts on television give prominence to crime news within their agendas since producers understand that this kind of information is attractive for the public; the authors observe that the way crime news is told defines the interpretive frame transmitted to viewers; and the authors describe how, in recent years, the production and presentation of crime news have changed as a result of the spread of digital technologies as sources of information. Research limitations: First, the study was conducted in just one country. Second, it does not specifically explore why the criteria of newsworthiness as described in the chapter are used. This question can only be explored by looking closely at the experiences of the actors in their sociohistorical context; therefore, a cultural study would need to look in depth at the historic characteristics of the security forces in Argentina and their relation with the press. Finally, a study on viewers’ opinions is needed in order to understand their interpretation of crime news in terms of meaning. Originality/value: The value of the study is to visualize the cultural specificities of the local newsmakers to understand the way they produce crime news. Whereas the study undoubtedly shares similar characteristics with news production in other countries, it focuses on the specific environment of local newsmakers and shows how the press experiences and visualizes crime and fear of crime in Argentina.